Measurement of unnecessary psychiatric readmissions: a scoping review protocol. Issue 7 (23rd July 2019) - Kim, Bo; Weatherly, Christopher; Wolk, Courtney Benjamin; Proctor, Enola K
Abstract : Introduction: Care transition for patients being discharged from inpatient mental healthcare to outpatient settings is a growing focus for healthcare delivery systems. Many studies of this inpatient to outpatient transition use the rate of postdischarge readmissions as a patient-level outcome measure to assess the quality of transition. However, it is unclear how studies define the measure, and whether there is a shared understanding by the field regarding which definition is appropriate for which circumstances. This scoping review thus aims to examine how published studies have approached measuring unnecessary psychiatric readmissions. Methods and analysis: The scoping review will be structured according to Levac et al 's enhancement to Arksey and O'Malley's framework for conducting scoping reviews. The protocol is registered through the Open Science Framework (https://osf.io/5nxuc/ ). We will search literature databases for studies that (1) are about care transition processes associated with unnecessary psychiatric readmissions and (2) specify use of at least one readmission time interval (ie, time period since previous discharge from inpatient care, within which a hospitalisation can be considered a readmission). Screening and review of articles will be carried out by two reviewers, first independently then involving a third reviewer as needed for consensus. We will assess review findings through both tabular and thematic analyses, noting prevalent trends in study characteristics and emergent themes across our reviewed studies. Ethics and dissemination: This work comes at a time of heightened interest by many mental healthcare systems in high-quality practices that structure their care processes towards effective inpatient to outpatient transitions. Findings will support the systems' careful examination of alternative potential transitional interventions, helping to ensure that their often limited quality enhancement resources are put to optimal use. We will focus on disseminating our findings to the healthcare community through strong communication infrastructures and connections with health system stakeholders that our multidisciplinary study consultants will foster throughout this study.